“So the Lights Have Bent”: Investigation of Pre-Service Teachers’ Conceptions of Science Through a Historical Narrative on the General Relativity Theory - Domingos, Fernando (2024)
Research in Science Education has advocated the use of historical narratives as a teaching and learning strategy across different levels of education. The main arguments supporting this approach are: i) the shared similarities between the human cognitive system and the structure of narratives; ii) the constant presence of narratives and their importance in human development. In education, historical narratives are viewed favorably because they stimulate emotional and cognitive connections with the reader/listener, either by eliciting feelings such as empathy and identification or by fostering greater engagement, understanding, and memorization of the narrated topics. In this study, conducted with pre-service physics teachers, we employed a historical episode from the Theory of General Relativity (T.G.R.) - the expedition of the total solar eclipse on May 29, 1919 - presented in the form of a historical narrative. The goal was to promote and contextualize discussions about science, its nature, its relationship with socio-historical context, and the influence of non-epistemic aspects on scientific practices. More specifically, by exploring the impacts of political conflicts on science and investigating the influences of World War I on the establishment of T.G.R., we characterized and problematized the epistemological conceptions of the teacher trainees regarding the relationships between science and politics. The construction of the historical narrative incorporated elements from previous research narratives and was guided by studies in the History and Philosophy of Science. The text was interrupted by "THINK!" questions to facilitate discussion and encourage students to take sides with the characters in the narrative, making them an integral part of the story and allowing them to experience some of the dilemmas and decisions involved in scientific work. The "THINK!" discussions were proposed and conducted in a way that allowed us to identify, classify, and problematize the epistemological conceptions of the research subjects. Data were collected through questionnaires (the "THINK!" questions themselves) and class discussions, which were recorded and transcribed to serve as the basis for data analysis. Subsequently, the conceptions were classified into the following analytical categories: rationalism, relativism, and moderate stances. To encompass other perceived conceptions, categories such as "common sense" and "naive relativism" were added. Overall, besides finding historical narratives as a strategy to guide and contextualize debates about the Nature of Science, we observed a prevalence of relativistic-leaning conceptions, emphasizing social aspects over the content of science in the analysis of issues related to the relationships between science and political conflicts. We also noted prescriptive and descriptive conceptions about these relationships, i.e., how they are and how they should be.